Estimation of PfRh5-based vaccine efficacy in asymptomatic Plasmodium falciparum patients from high-endemic areas of Tanzania using genetic and antigenicity variation screening - Jun, Hojong; Mazigo, Ernest; Lee, Wang-Jong; Louis, Johnsy Mary; Syahada, Jadidan Hada; Fitriana, Fadhila; Heo, Jin; Kim, Yeonkyung; Kwon, Boeun; Muh, Fauzi; Lu, Feng; Ahmed, Md Atique; et al. (Frontiers in Immunology, 2024)
BackgroundPlasmodium falciparum is the most lethal malaria parasite. Recent phase 1b vaccine trials using P. falciparum reticulocyte binding protein homolog 5 (PfRh5) demonstrated safety and promising efficacy in preventing merozoite invasion. PfRh5 has emerged as a strong vaccine candidate due to its essential role in merozoite invasion and limited sequence variation. For effective malaria vaccine development, especially in high-transmission settings, strain-transcending activity must be considered. Ongoing monitoring of antigenic variation and natural immune responses is important to estimate vaccine efficacy across geographically diverse populations.MethodsSamples for this study were collected from four villages in each of the Kigoma and Geita regions, known malaria transmission hotspots in Tanzania. This community-based cross-sectional study was conducted from December 2022 to July 2023. Genetic variation and natural selection pressure on pfrh5 were analyzed in 164 asymptomatic P. falciparum isolates. The humoral immune response to PfRh5 was also assessed using a protein microarray with 242 sera samples from asymptomatic patients in the same population. Finally, a correlation analysis was conducted to compare pfrh5 genetic variation with the humoral immune response.ResultsThe results revealed that pfrh5 was well conserved, but novel non-synonymous mutations were found at D65H, H170N, and I227M. Additionally, natural selection metrics indicated the potential for positive selection and a recent population expansion of PfRh5 in the study area, both of which could influence vaccine effectiveness. Antigenicity screening revealed variable sensitivity, ranging from 3.3% in Bunyambo to 82.8% in Rwantaba, with no significant relationship between antigenicity and parasitemia, haplotypes, or gender. However, age was significantly associated with humoral immune response (ρ = 0.170, p = 0.008).ConclusionsThese findings underscore the need for future PfRh5-based vaccines to consider for increasing genetic variation and geographical differences in humoral immune responses.